PENGARUH CELEBRITY ENDORSEMENT, PENGETAHUAN PRODUK, KEMASAN PRODUK DAN PERCEIVED VALUE TERHADAP PURCHASE INTENTION: PENGARUH CELEBRITY ENDORSEMENT, PENGETAHUAN PRODUK, KEMASAN PRODUK DAN PERCEIVED VALUE TERHADAP PURCHASE INTENTION - Andriyani, Bianka; Arifianto, Fikki Laili (Kajian Ekonomi dan Bisnis, 2023)
This research aims to test the effect of celebrity endorsement, product knowledge, product packaging, and perceived value on purchasing interest in the energy drink brand Red Bull GmbH, the research location is in Indonesia. The method used in this research is multiple regression analysis using primary data obtained from the distribution of questionnaires using google form media online. The sample in this research was taken with a purposive sampling technique with the criteria for age 15-50 years old men and women who have information about the Red Bull brand on social media or other online media. The sample in this research was obtained as many as 100 respondents, then the respondent data was processed using the SPSS 26 program. The results of the research conducted by the author prove that there is an effect of celebrity endorsement, product knowledge, product packaging, perceived value on purchasing interest. Keywords: Celebrity Endorsement, Product knowledge, Product packaging, Perceived Value, Purchase Intention